QOLP-10. A LONGITUDINAL OBSERVATIONAL STUDY OF EXERCISE BEHAVIOR IN GLIOBLASTOMA PATIENTS TREATED WITH TUMOR-TREATING FIELDS. (12th November 2021) - Peters, Katherine; Affronti, Mary; Kim, Jung-Young; Patel, Mallika; Johnson, Margaret; Bartlett, David; Cort, Nicole; Lipp, Eric; Iden, Deborah; Broadwater, Gloria; Herndon, James; Landi, Daniel; et al.
Abstract: Glioblastoma (GBM) patients can use tumor-treating fields (TTFs) with adjuvant temozolomide (TMZ) to treat their disease. TTFs involve wearing transfixed transducers to the shaved scalp, and the transducers are wired to a battery pack that is either fixed or carried (weighing 2.7 pounds). EF-14 clinical trial did evaluate health-related quality of life with standardized patient-report outcome measures but did not measure exercise behavior. We sought to evaluate the exercise behavior of GBM patients using TTFs. We consented GBM patients who intended to use TTFs with adjuvant TMZ after completion of chemoradiation. After informed consent and before starting TTFs, patients completed a self-administered questionnaire, Godin Leisure-Time Exercise Questionnaire, to assess exercise behavior/physical function. To calculate our primary outcome of total exercise behavior, the frequency of exercise sessions per week within each intensity category was multiplied by the average reported duration, weighted by an estimate of the MET, summed across all intensities, and expressed as average MET-hr/wk. Prior work has defined that physical function can be compared as < 9 MET-h/wk vs. ≥ 9 MET-h/wk. We evaluated at baseline and up to 24-week exercise behavior in patients with TTFs vs. historical controls not using TTFs. We enrolled 19 total GBM patients, with 14 proceeding to use TTFs. Of the 14 patients on TTFs, seven patients (50%) completed ≥ 9 MET-h/wk of exercise, and this level was maintained 8, 16, and 24 weeks after starting TTFs. Six months after the completion of chemoradiation, mean MET-h/wk was decreased in the TTFs group (n=6) (10.71 sd=7.06) vs. historical controls (n=38) (27.35 sd=46.94). TTFs did not interfere with exercise behavior in our GBM cohort, but when compared to GBM patients not utilizing TTFs, there could be a long-term impact on exercise behavior. More research is needed to evaluate exercise behavior in GBM patients using TTFs.